Pemberdayaan Peternak Ayam Petelur Melalui Pelatihan Edupreneurship Berbasis Diversifkasi Pakan Ternak Di Desa Pattallikang, Kecamatan Manuju, Kabupaten Gowa - Baharuddin, Andi; Alisyahbana, Andi Naila Quin Azizah; Hardianti, Hardianti (Journal Of Human And Education (JAHE), 2024)
Empowering laying hen farmers is one of the keys to increasing productivity and economic welfare in the livestock sector. This study aims to explore the effectiveness of edupreneurship training based on verified animal feed in improving the skills and knowledge of laying hen farmers. Through this training, farmers are introduced to the basic concepts of sustainable and effective livestock business management, with an emphasis on the importance of scientifically verified animal feed to support the health and productivity of laying hens. The methodology used in this study involved a six-month structured training, which included materials on optimal feed formulation, livestock health management, and livestock product marketing strategies. The training participants were laying hen farmers from various regions, who were randomly selected and divided into control and experimental groups. The results of the training showed a significant increase in the knowledge and skills of farmers regarding good feed formulation and livestock health management. In addition, there was a significant increase in egg productivity and farmer income after participating in the training. These findings emphasize the importance of an edupreneurship approach based on verified animal feed as an effective strategy for farmer empowerment. The conclusion of this study is that edupreneurship training based on verified animal feed can effectively improve the skills, knowledge, and economic welfare of laying hen farmers. Therefore, this training program is recommended to be expanded to more farmers to support the development of the laying hen farming sector as a whole.